Emerging and re-emerging zoonotic viral diseases in Southeast Asia: One Health challenge - Paola Mariela Saba Villarroel; Paola Mariela Saba Villarroel; Nuttamonpat Gumpangseth; Nuttamonpat Gumpangseth; Thanaphon Songhong; Thanaphon Songhong; Sakda Yainoy; Arnaud Monteil; Arnaud Monteil; Pornsawan Leaungwutiwong; Dorothée Missé; Sineewanlaya Wichit; et al. (Frontiers Media S.A., 2023)
The ongoing significant social, environmental, and economic changes in Southeast Asia (SEA) make the region highly vulnerable to the emergence and re-emergence of zoonotic viral diseases. In the last century, SEA has faced major viral outbreaks with great health and economic impact, including Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), arboviruses, highly pathogenic avian influenza (H5N1), and Severe Acute Respiratory Syndrome (SARS-CoV); and so far, imported cases of Middle East Respiratory Syndrome Coronavirus (MERS-CoV). Given the recent challenging experiences in addressing emerging zoonotic diseases, it is necessary to redouble efforts to effectively implement the "One Health" initiative in the region, which aims to strengthen the human-animal-plant-environment interface to better prevent, detect and respond to health threats while promoting sustainable development. This review provides an overview of important emerging and re-emerging zoonotic viral diseases in SEA, with emphasis on the main drivers behind their emergency, the epidemiological situation from January 2000 to October 2022, and the importance of One Health to promote improved intervention strategies.